2006
DOI: 10.1111/j.1528-1167.2006.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Children/Teens with Epilepsy Compared with That in Their Siblings without Epilepsy

Abstract: Summary:Purpose: To determine (a) whether children and teens with epilepsy participate in less physical activity and have higher body mass index (BMI) percentiles for age than do their siblings without epilepsy; and (b) what epilepsy-specific factors limit their participation.Methods: Patients 5-17 years, with a ≥3 month history of epilepsy, a development quotient ≥80, no major motor or sensory impairments, and at least one sibling without epilepsy in a similar age range, were identified from the Neurology Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 19 publications
5
68
1
6
Order By: Relevance
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
“…The abundance of research exploring the benefits of and barriers to exercise for people with epilepsy has been primarily quantitative and medico-scientific [4,8,9,10] , leaving an omission in our understanding of the first-hand exercise experiences of people with epilepsy. Therefore, through the use of narrative inquiry, this research aims to present the psychosocial impact of exercising with epilepsy over time.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown physical exercise to be beneficial for most people with epilepsy (PWE) because of the positive effects on seizure control and well-being (Nakken et al 1990, Wong andWirrell 2006). Although epilepsy is one of the most common neurological disorders (Arida et al 2009),2 the lack of first-person experiences raised the question as to whether the positive effects of exercise (Sirven 2009, Arida et al 2013) hold true to the experiences of PWE.…”
Section: Epilepsy and Exercisementioning
confidence: 99%
“…However, children with severe impairments often have physical limitations as well as oral motor problems that affect feeding. 30,31 Stimulant drugs can also affect feeding by decreasing appetite, which may in turn decrease weight. 32 In this study, patients on stimulant psychotropics exhibited a lower mean BMI Z-score close to 1 full unit on average (adjusted) compared to patients on no medication.…”
Section: Predictors Of Bmimentioning
confidence: 99%